Economic and environmental evaluation of recombinant enzyme production - Jamaluddin, Mohd Jamil Aizat; Azmi, Azlin Suhaida; Sulaiman, Sarina; Jimat, Dzun Noraini; Othman, Muhd. Ezza Faiez; Amid, Azura (Springer International Publishing, 2015)
Economic and environmental evaluation on three different throughputs and comparison between these throughputs were presented. Comparisons are based on simulation of 10, 100 and 1000 kg/batch of recBromelain using SuperPro Designer v8.5. The economic analysis shows that 100 kg/batch gives the most competitive price and maintaining a sizeable profit gross margin of 28.21 %. A positive ROI of 18.41 % and minimal payback time of 5.43 years is predicted from 100 kg/batch of production. Environment analysis showed that total waste and energy consumption increased as production size increased. This simulation information will assist to predict the cost and environment impact at different size of productions.